Integrating Hadith in Da'wa Film: Analyzing 'Memuliakan Tamu' through Branston and Stafford's Production-Organization Framework - Nurhabliyah (El Madani: Jurnal Dakwah dan Komunikasi Islam, 2025)
The development of Indonesian da’wa movie have been fluctuate through several decades. In 2009, da’wa through film had reached its glory by the production of “Ketika Cinta Bertasbih.” In the other hand, YouTube platform had been supporting the globe to watch movie online. The aim of this study is to explain how the movie titled “Memuliakan Tamu,” produced by Achi TM Pictures uploaded in YouTube through Islamic Short Movie Channel, could be guidance for Muslims to be ideal hostess either guest. Research method which applied in the study is qualitative method, where the data obtained by observation and literature. The data analysis is using Production and Organization by Stafford and Branston combined with Hadiths about silaturahiim and honouring the guest. The result shows that the movie use several Hadiths such as; (1) how to accompany guest, (2) serve guest with the food they like the most, (3) to regale the guest, (4) the blessing in receiving guest, (5) the blessing of silaturahiim. This film also had applied the producer of movies; production; preproduction, production and post production. If movie production and organization consistently look up to Al Quran and Hadiths, then movie will become not only media performance but also guidance for existence.